Zr- and Hf-based metal-organic frameworks: Tracking down the polymorphism - Bon, Volodymyr; Senkovska, Irena; Baburin, Igor A.; Kaskel, Stefan (Crystal Growth and Design, 2013)
Six novel Zr(IV)- and Hf(IV)-based MOFs, namely DUT-67, DUT-68, and DUT-69 (DUT, Dresden University of Technology) were obtained using a modulated synthesis approach with the acetic acid as a modulator and the bent 2,5-thiophenedicarboxylate (tdc2-) as a ligand. The modulator not only increases the size of the MOF crystallites but also plays a role of a structure directing agent, affecting both the secondary building unit (SBU) connectivity and topology of the resulting frameworks. The structure of DUT-67 is based on the reo underlying net, characteristic for its cuboctahedral and octahedral pores and is therefore isoreticular to DUT-51. The DUT-68 material has a more complicated hierarchical pore system including rhombicuboctahedral mesopore, surrounded by cuboctahedral, square-antiprismatic and octahedral microcages. DUT-69 is the first example of Zr-based MOF containing 10-connected SBU. DUT-69 has bct topology, possessing octahedral cages and channels running along one crystallographic direction. In accordance with X-ray single crystal analysis, the pores of DUT-67 and DUT-68, which were obtained at high modulator concentrations, are partially occupied by additional clusters. All novel materials are found to be robust, hydrophilic, chemically, and thermally stable. The BET specific surface area amounts to 1064 and 810 m2· g-1 for DUT-67(Zr) and DUT-67(Hf), 891 and 749 m2· g-1 for DUT-68(Zr) and DUT-68(Hf), and 560 and 450 m 2·g-1 for DUT-69(Zr) and DUT-69(Hf), respectively. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20